2019
DOI: 10.1016/j.vaccine.2017.09.093
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the oral rabies virus vaccine strain SPBN GASGAS in foxes and raccoon dogs

Abstract: To test the immunogenicity and efficacy of a new oral rabies virus vaccine strain SPBN GASGAS in wildlife target species, one group of foxes and two groups of raccoon dogs were offered a bait containing 1.7 ml of the vaccine (10 FFU/ml; 10 FFU/dose) and subsequently challenged approximately 180 days later with a fox rabies virus isolate. One group of raccoon dogs (n=30) received the same challenge dose (10 MICLD/ml) as the red foxes (n=29). The other group with raccoon dogs (n=28) together with 8 animals that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 59 publications
4
23
0
Order By: Relevance
“…While the relatively short incubation periods of 12–26 days observed after high dose infection are within the lower bounds of the expected range and are comparable to those of carnivorous reservoir species, Kudus and cattle 12 , 19 , 31 – 34 , the extremely long incubation periods of 93–245 days after low dose infection are remarkable, particularly against the background of the same route of infection and the fact that the difference in viral dose was just two log 10 steps (Fig. 4 ).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…While the relatively short incubation periods of 12–26 days observed after high dose infection are within the lower bounds of the expected range and are comparable to those of carnivorous reservoir species, Kudus and cattle 12 , 19 , 31 – 34 , the extremely long incubation periods of 93–245 days after low dose infection are remarkable, particularly against the background of the same route of infection and the fact that the difference in viral dose was just two log 10 steps (Fig. 4 ).…”
Section: Discussionmentioning
confidence: 67%
“…However, it is the first time that such a proof-of-concept study has ever been conducted in an herbivorous species such as Kudus. The vaccine strain SPBN GASGAS has shown to be efficacious in several animal species like red foxes ( Vulpes vulpes ), raccoon dogs ( Nyctereutes procyonoides ), raccoon ( Procyon lotor ) and small Indian mongoose ( Herpestes auropunctatus ) 19 , 52 , 53 . However, striped skunks ( Mephitis mephitis ) seem to be rather refractory to vaccination through the oral route in a vaccine virus titer dependent manner 47 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be concluded that the oral rabies virus vaccine SPBN GASGAS meets the latest revised safety requirements of the European Pharmacopoeia ( 1 ). The efficacy of this vaccine strain in the target species, red fox and raccoon dog, has been previously shown ( 32 ). Hence, this third generation oral rabies virus vaccine has retained the immunogenic properties of its parental strain SAD B19 but has a greatly improved safety profile in comparison to first and second generation oral rabies virus vaccines.…”
Section: Discussionmentioning
confidence: 93%
“…In the case of free range farms, animals should be protected from infection by wild boars, e.g., by a solid wall. Possibly, in far future HEV can be controlled and eliminated from the wild animals using oral vaccination as was successfully done in oral rabies vaccination campaigns for foxes and raccoon dogs [77]. In addition to wild boars, other wild animals can be HEV-positive and can transmit the virus.…”
Section: Measures To Prevent Hev Transmissionmentioning
confidence: 99%